Effect of irrigation methods and testing some rice cultivars against growth, root development and yield on rainfed Ultisols of Aceh Besar. Issue 1 (November 2021) - Helmi, H; Zakaria, S; Efendi,; Munawar, A A; Aulia, R
Abstract: The main obstacle in rice cultivation on dryland is the limitation of water availability and large fluctuation of groundwater availability. It causes plant metabolic processes to be hampered. The threat of such natural conditions can be overcomed by intensifying and using superior cultivars to adapt widely to the environment, such as being resistant to drought. This study aims to determine the effect of irrigation methods and the response of several different cultivars to growth, yield potential, and rice root systems. This research using a Split Plot Design pattern. The factors examined in this study were irrigation methods, which consisted of 3 levels of treatment, namely continuous irrigation (P1), intermittent irrigation (P2), and sprinkler irrigation (P3). Variety factors consisted of 4 levels, namely: Batutegi (V1), Situ Patenggang (V2), Inpago 5 (V3), and Sanbei (V4), so there were 12 treatment combinations with three repetitions of 36 treatment plot units. The results showed that the continuous and intermittent irrigation methods gave the highest yield per hectare and had the same weight, while the sprinkler gave the lowest yield per hectare, although not significantly different from other irrigation methods. The cultivar that gave the highest yield per hectare was Sanbei, while the lowest was Situ Patenggang, and the cultivar that gave the highest 1000 grain weight was Inpago-5, while the lowest was Sanbei, although it was not significantly different from other cultivars.